Ground-level Concentration of Ozone in Ambient Air in Chittagong (Bangladesh) City - Begum, BA; Saroar, G; Nasiruddin, M; Biswas, SK (Bangladesh Journal of Scientific and Industrial Research, 2012)
The distribution of the ground-level ozone concentration in Chittagong city was continuously monitored at air monitoring station in Chittagong city during period of December 2006 to December 2007. The results of this study have revealed that the ground-level ozone concentration in Chittagong city varied from season to season. The highest ground-level ozone concentration was found in winter. The groundlevel ozone concentration has also a clear diurnal cycle - with higher values in the daytime and notably becomes zero at night depending on season. Meteorological conditions are known to influence the formation and dispersion of ground-level ozone concentration. At temperature lower than 20°C, the concentration of ozone becomes high where as at high temperature (> 30°C), the concentration becomes low. It has also been found that at low wind speed, the ozone concentration is high and at high wind speed, the concentration becomes low due to dispersion. The results also establish that the during the study periods, the ozone concentration was below the Bangladesh National Ambient Air Quality Standard (BNAAQS) of 80 ppb (annual average). DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10729 Bangladesh J. Sci. Ind. Res. 47(1), 83-88, 2012